The complexity of an artwork affects the subjective perception of time and bimanual motor activity performed in the presence and absence of music of the patients with Parkinson\'s disease - Motta, Márcia Regina (2021)
The time passage is perceived in a multitasking context. Patients with Parkinson\'s disease (PwPD) due to motor, cognitive and perceptual disorders may present alterations in the judgment of duration, especially when more than one task needs to be performed at the same time and some factors may influence more than others and lead to improvement or the deterioration of performance. This research aims to examine the effects of music on the time perception and on the manipulation of artworks with different levels of complexity performed by PwPD in conditions with (ON) and without (OFF) dopaminergic medication. For this, two sculptures differing in level of complexity, with the number of pieces being the differentiating factor: more complex artwork (MC) containing 10 pieces, and less complex artwork (LC) containing six pieces. They were manipulated by PwPD and disease-free participants. The exploration took place in the presence or absence of music during the 45s interval. Manipulation time was reproduced and verbally estimated. PwPD were tested first in the OFF condition and then in the ON medication. The frequency of the exploratory movement was analyzed. Data were submitted to a mixed-model repeated measures ANOVA with p<0.05. The results showed that the level of complexity of the artworks affected the participants\' time perception. MCA manipulation time was underestimated in temporal reproduction and overestimated in verbal estimation. The manipulation time of the LCA, despite also having been underestimated in the temporal reproduction and overestimated in the verbal estimation, was judged as greater in relation to the MCA. These results were independent of the group, medication condition, and the presence or absence of music. There was an effect of the medication on the time perception by PwPD. When in OFF, they performed similarly to participants without PD, which did not happen when they were in ON. The group effect on the frequency of movements performed by the participants was observed. PwPD had lower movement frequency than participants without PD. Despite this, the medication influenced the motor activity, increasing the movement frequency. There was no effect of music on the movement frequency and on the time perception of participants with and without PD. The findings point to the effect that properties, such as the level of complexity of artworks, have on the temporal judgment of participants. For PwPD, the medication did not seem to influence temporal information processing, but it did seem to affect motor activity. The music proved neither impair nor improve the PwPD\'s perceptual and motor performance. It is likely that the complexity of the artwork was configured as an aspect that retained the participants\' attention and diverted it from the passage of time, and the higher frequency of PwPD movements when they were medicated may have contributed to the temporal judgment.